Prevalence and factors associated with hypertension: a community based cross-sectional study among adults in an urban area of Puducherry, South India - Paul, Pramila J.; Samson, Rebecca; William, Annie; Akila, Bridgitte; Purty, Anil J.; Bazroy, Joy (International Journal Of Community Medicine And Public Health, 2017)
Background: The prevalence of hypertension and other non-communicable diseases in India are on the increasing trend. Hypertension is a major public health problem in India. This study aimed to estimate the prevalence and associated factors of hypertension in an urban area of Puducherry, South India. Methods: A community-based cross-sectional study was carried out among adults in an urban area of Puducherry, South India, between Oct 2013 to Nov 2013. A total of 236 adults aged ≥ 35years were selected and data was collected using piloted questionnaire. Blood pressure was measured following standard technique. Results: Out of 236 participants 123(52.1%) were found to be hypertensives. Among the hypertensives, nearly one fourth 32(24%) of them were undiagnosed hypertensives. Advanced age, male gender, housewives compared to their counterparts, family history of hypertension, alcohol intake, sedentary lifestyle, and abdominal obesity (among females) were significantly associated with hypertension. Conclusions: The prevalence of hypertension is found to be high. Regular health education programme to raise awareness and community-based screening programme should be given priority for early detection of hypertension and prevention of complications.